Parasites of juvenile Salminus brasiliensis and Brycon orbignyanus (Characiformes, Bryconidae) in the middle Paraná River, Argentina (Acta Scientiarum. Biological Sciences, 2023)
Piscivorous Salminus brasiliensis and herbivorous/omnivorous Brycon orbignyanus often form mixed schools in the same habitats. The aims of this study were: (a) to analyze and compare ecto- and endoparasite communities in juvenile S. brasiliensis and B. orbignyanus in the Middle Paraná River, Argentina; and (b) to evaluate the possible relationships between degree of parasitic infestation and body condition (Kn) of the fish. Fish necropsy was performed in search of endo- and ectoparasites, which were mounted in permanent or semi-permanent preparations for taxonomic study using helminthological techniques. A total 24 macroparasite taxa were recorded from the two host species. The parasitic infracommunities of both hosts were competitively structured. Ectoparasite communities were more similar than endoparasite communities. The abundance of parasitic species was not correlated with the standard length, weight and Kn of host individuals, except for the abundance of the copepod E. lacusauratus in the host S. brasiliensis, which was positively related to fish condition. New records of parasites were observed for native hosts, extending the geographic range of several species already known in the Upper Paraná River. The general structure of parasite communities can be determined by several factors, such as parasite-host relationship, host trophic level, and environment. In concordance with the similarity in habitat preferences, and the strong differences in trophic preferences, ectoparasite communities were found to be more similar than endoparasite communities between the two host species.